Determinants That Influence Audit Delay - Tanujaya, Kennardi; Nuriah, Sinta (Global Financial Accounting Journal, 2023)
Purpose - This study was conducted to identify the factors that affect audit delays and things that cause delays in audited financial statements. This study uses variables such as firm size, audit opinion, auditor size, profitability, leverage, board of commissioners’ size, independent commissioner size, CEO tenure, and CEO expertise. Research Method - Data from the annual financial statements of firms listed on the Indonesia Stock Exchange were utilized as the sample in this study. A total of 1,960 data samples were obtained, covering the years 2016 to 2020. Purposive sampling was used in this study's data gathering process, and quantitative data were collected. Findings - The results of this study found that the variables of firm size, audit firm size, profitability, leverage, board size, CEO tenure, and CEO expertise did not affect audit delays, while audit opinion variables had a significant negative effect and the independent board of commissioners variables had a significant positive effect against audit delayss. Implication - Companies can use the study's findings as a guide for assessing the quality of financial statement presentation and publish financial reports on time, can assist auditors in conducting audit reports to determine the determinants that affect audit delays, and can be taken into consideration for investors in investing in companies experiencing financial problems audit delay.